Development of Multiplex PCR Detection by Pooled Sample in Alpha-thalassemia 1 - Jearakul, Wipavadee; Khamsaen, Junchay (Journal of Health Science of Thailand, 2018)
Alpha-thalassemia 1 is a genetic disorder with imbalanced globin gene synthesis which leads to anemia. The prevalence of two types of alpha-thalassemia in Thailand (SEA and THAI) found approximately five percent. Molecular detection of alpha-thalassemia can be made by multiplex polymerase chain reaction (PCR) using primers adjacent to the deletion breakpoint and visualization of the amplified fragments on ethidium bromide stained after run agarose gel electrophoresis which is costly. Pathology section of Regional Medical Science Center Ubon Ratchathani then developed this method by pooled sample before detection. It was found that the accuracy, precision and reproducibility of SEA, THAI and both of SEA and THAI type are one hundred percent in dilution 1:10. While the limit of detection of SEA type is equal or lower than 1:100 and THAI type is 1:40. So this development technique will reduce the cost and time to detect Alpha-thalassemia 1 by multiplex PCR.